LEARNING ORGANIZATION PADA PUSAT PELATIHAN DAN PENGEMBANGAN DAN KAJIAN MANAJEMEN PEMERINTAHAN LAN RI MAKASSAR - Harnisah, Yuli; Malik, Ihyani; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2023)
This study is to find out how to apply and describe and analyze Learning Organizations at the Center for Training and Development of Government Management Studies Makassar State Administration. This type of research is a qualitative descriptive research that is sourced from primary and secondary data. The result of the research shows that the learning organization at Puslatbang KMP LAN RI Makassar is 1) learning organization that supports the implementation of the organization, namely learning culture, namely learning culture that prioritizes sharing. process, namely employees are given the opportunity to become facilitators in a training tools and techniques, namely the facilities can be said to be good and learning methods and learning methods such as interactive learning, skills and motivation namely employees are forced to catch up so that they can improve the individual abilities of employees.